2020
DOI: 10.33633/jpeb.v5i2.3270
|View full text |Cite
|
Sign up to set email alerts
|

Brand Image as a Mediation of Electronic Word of Mouth on Purchasing Intention of Laneige

Abstract: The purpose of the study was to know and analyze the role of brand image as a mediator of the impact of the Electronic Word of Mouth on purchasing intention of Laneige’s product. A sample of 100 respondents used a purposive sampling technique. The type of test used to analyze the data was the validity and reliability test. The data analysis technique used is path analysis. The results of  the Electronic Word of Mouth study have a significant and positive effect on brand image and purchasing intention. The Bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
1
0
4
Order By: Relevance
“…The fifth finding indicates that brand image toward purchase intention has a significant positive effect. This aligns with previous research (Chintia Pramesti & Rahanatha, 2018;Narendra Bagaskara & Ngatno, 2021;Nuseir, 2019;Prastiyani & Suhartono, 2020;Putra et al, 2020;Supradita et al, 2020;Wahyoedi & Effendi, 2021). It was found that a positive perception of the brand image is closely associated with consumers' purchase intent.…”
Section: Resultssupporting
confidence: 91%
“…The fifth finding indicates that brand image toward purchase intention has a significant positive effect. This aligns with previous research (Chintia Pramesti & Rahanatha, 2018;Narendra Bagaskara & Ngatno, 2021;Nuseir, 2019;Prastiyani & Suhartono, 2020;Putra et al, 2020;Supradita et al, 2020;Wahyoedi & Effendi, 2021). It was found that a positive perception of the brand image is closely associated with consumers' purchase intent.…”
Section: Resultssupporting
confidence: 91%
“…Perceived quality, defined as the consumer's perception of a product's overall quality and superiority related to its intended purpose (Zeithaml, 1988), was also found to be an influential antecedent of Muslims' purchase intention (e.g., Halim & Kiatkawsin, 2021). Finally, electronic word of mouth (eWoM) is an important source of product information for Muslim consumers (see Table 1), and eWoM directly influences purchase intention (e.g., Lubis & Ariyanti, 2020; Supradita et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Citra merek suatu cara konsumen atau pelanggan dalam mempertimbangkan untuk melakukan suatu transaksi dalam pembelian pada produk yang diinginkan dan jasa yang akan digunakan. (Supradita et al, 2020). Adapun indikator penting dalam citra merek yang ada pada setiap perusahaan yaitu citra dalam perusahaan yang harus terus dijaga, citra merek dari pengguna atau konsumen dan yang paling penting citra dari setiap produk yang ada (Alrwashdeh et al, 2019).…”
Section: Kajian Pustakaunclassified
“…Semakin terkenal citra baik dari restoran tersebut akan menjadi pertimbangan seperti KFC, McDonal's, Richeese Factory dan A & W yang telah mempunyai citranya masing-masing dan kini bersaing untuk lebih ditingkatkan lagi. Hasil uji penelitian yang didapat sama dan sesuai dengan jurnal dari (Arif, 2019;Benowati & Purba, 2020;Putra et al, 2020;Putri, 2018;Setiawan et al, 2020;Supradita et al, 2020;Soegeng Wahyoedi et al, 2021).…”
Section: Tabel 6 Hasil Uji Indirect Effectunclassified
See 1 more Smart Citation